Conservation of Archaeal C/D Box sRNA-Guided RNA Modifications - Breuer, Ruth; Gomes-Filho, Jose-Vicente; Randau, Lennart (Frontiers in Microbiology, 2021)
Post-transcriptional modifications fulfill many important roles during ribosomal RNA maturation in all three domains of life. Ribose 2'-O-methylations constitute the most abundant chemical rRNA modification and are, for example, involved in RNA folding and stabilization. In Archaea, these modification sites are determined by variable sets of C/D box sRNAs that guide the activity of the rRNA 2'-O-methyltransferase fibrillarin. Each C/D box sRNA contains two guide sequences that can act in coordination to bridge rRNA sequences. Here, we will review the landscape of archaeal C/D box sRNA genes and their target sites. One focus is placed on the apparent accelerated evolution of guide sequences and the varied pairing of the two individual guides, which results in different rRNA modification patterns and RNA chaperone activities.